Preliminary factor analysis of the O’Kelly Women Beliefs Scale in a US sample - Heman Contreras, Arturo; Instituto de Terapia Cognitivo Conductual en México (2011)
Using a Rational Emotive Behavior Therapy framework, the O’Kelly Women Beliefs Scale (O’Kelly, in press) was originally constructed in Australia to measure sex-role beliefs women may develop through sex-role stereotyping. Factor analysis of the 92 original items showed that 64 items loaded into a single component that accounted for 18.2% of the variance in a sample of 974 Australian women. The present exploratory study examined the psychometric properties of the OWBS in a sample of 202 women born and living in the US. A varimax rotation with cutoff eigenvalues of 3, showed that 37 items loaded into 3 components which accounted for 58.48% of the variance. The items were subsequently grouped into two factors: Irrationality, with a total of 27 items was created by merging component 1 and 3 (Pearson’s r = 0.8 between them), and Rationality, with the 10 items from component 2. Analyses indicated a Cronbach’s alpha of 0.91 for Factor 1, and a Cronbach’s alpha 0.74 for Factor 2. Results indicate that this version of the instrument may be used to evaluate both the rational and irrational content of sex-role beliefs of women born in the US.